ICEBERG study: an indirect adjusted comparison estimating the long-term benefit of esketamine nasal spray when compared with routine treatment of treatment resistant depression in general psychiatry - Oliveira-Maia, Albino J.; Morrens, Joachim; Rive, Benoit; Godinov, Yordan; Cabrieto, Jedelyn; Perualila, Nolen; Barbreau, Sebastien; Mulhern-Haughey, Siobhán (Frontiers in Psychiatry, 2023)
Treatment resistant depression (TRD) affects 10-30% of patients with major depressive disorder. In 4-week trials, esketamine nasal spray (NS) was efficacious versus placebo when both were initiated in addition to a new selective serotonin or serotonin-norepinephrine reuptake inhibitor. However, comparison with an extended range of real-world treatments (RWT) is lacking.ICEBERG was an adjusted indirect treatment comparison using propensity score-based inverse probability weighting, performed on 6-month response and remission data from patients receiving esketamine NS plus oral antidepressant from the SUSTAIN-2 (NCT02497287; clinicaltrials.gov) study, compared with patients receiving other RWT from the European Observational TRD Cohort (EOTC; NCT03373253; clinicaltrials.gov) study. SUSTAIN-2 was a long-term open-label study of esketamine NS, while the EOTC was conducted at a time when esketamine NS was not available as RWT. Threshold and sensitivity analyses were conducted to assess how robust the primary analyses were.Patients receiving esketamine NS had a higher probability of 6-month response (49.7% [95% confidence interval (CI) 45.6-53.9]) and remission (33.6% [95% CI 29.7-37.6]) versus patients receiving ] and 18.2%, [95% CI 13.9-22.5], respectively), according to rescaled average treatment effect among treated estimates. Resulting adjusted odds ratios (OR) and relative risk (RR) favoured esketamine NS over RWT for 6-month response (OR 2.756 [95% CI 2.034-3.733], p<0.0001; RR 1.882 [95% CI 1.534-2.310], p<0.0001) and remission p<0.0001;], p<0.0001). Threshold analyses suggested that differences between the two studies were robust, and results were consistent across extensive sensitivity analyses.ICEBERG supports that, at 6 months, esketamine NS has a substantial and significant benefit over RWT for patients with TRD. While results may be affected by unobserved confounding factors, threshold analyses suggested these were unlikely to impact the study conclusions.